88.7k views
5 votes
Which of the following is equivalent to the quadratic equation below after completing the square

X^2+6x-3=12

A. (X+6)^2=12

B.(x+6)^2=9

C.(x+3)^2=24

D.(x+3)^2=9

1 Answer

1 vote

Answer:

C

Explanation:

To complete the square add c t the other side of the equal sign. Then divide the middle term b by 2 and square it.


x^2+6x-3=12\\x^2 + 6x +(?)=12+3\\x^2+ 6x + (3^2) = 15 + (3^2)\\x^2 + 6x +9 = 24

After finding the new c term and adding it to both sides, write the left side in factored form.


x^2 + 6x +9 = 24\\(x+3)^2 = 24

User Kamal
by
5.6k points